(untitled) (Research, Society and Development, 2022)
The lucerne productive and nutritional potential make it the most used forage legume worldwide. This wide use leads genetic improvement programs to increasingly select the main requirements for a given edaphoclimatic condition. However, in Brazil, the research on genetic improvement of lucerne has been limited over the years, which has hindered the production of this species and the domination of other legumes in animal production, as estilosantes and pigeon pea. This literature review aimed to present results from countries such as New Zealand and Australia that lead the world ranking, as weel as Argentina, in the cultivation of this crop and that can be used as showcase to understand the management of lucerne. From extensive bibliometry analyses in the period between 1963 and 2021, variables as persistence and phyllochron in these countries indicate that it is possible to produce lucerne with similar productivity, longevity and quality in Brazil. Nevertheless, to leverage this production, not only genetic improvement should be aimed, but also research and dissemination of knowledge on the ideal management of defoliation and, mainly, on the choice of the genotype and dormancy level to be cropped by the producer.